2020
DOI: 10.1002/jcp.29973
|View full text |Cite
|
Sign up to set email alerts
|

NPY promotes macrophage migration by upregulating matrix metalloproteinase‐8 expression

Abstract: Macrophage migration is thought to participate in obesity-related cardiovascular diseases. Matrix metalloproteinase-8 (MMP-8) possesses proteolytic activity on the extracellular matrix (ECM), which promotes macrophage migration to the site of vascular injury. Neuropeptide Y (NPY) is a bioactive peptide involved in MMP ex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…CFU-M is further differentiated into mononucleated osteoclasts and subsequently fused to multinucleated osteoclasts, then fully matured upon a cognate interaction with osteoblasts (53). Wu et al reported that NPY greatly increased the amount of RAW264.7 cell (mouse leukemic monocyte macrophage cell line) migration at different concentrations, and this effect can be diminished by the Y1R antagonist and ERK1/2 inhibitor, which suggest that NPY promotes osteoclast migration through Y1R and ERK1/2 activation (22). NPY has also been shown to exhibit an inhibitory effect on isoprenaline-induced osteoclastogenesis by suppressing RANKL expression in mouse bone marrow cells (54).…”
Section: Npy and Bone Resorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFU-M is further differentiated into mononucleated osteoclasts and subsequently fused to multinucleated osteoclasts, then fully matured upon a cognate interaction with osteoblasts (53). Wu et al reported that NPY greatly increased the amount of RAW264.7 cell (mouse leukemic monocyte macrophage cell line) migration at different concentrations, and this effect can be diminished by the Y1R antagonist and ERK1/2 inhibitor, which suggest that NPY promotes osteoclast migration through Y1R and ERK1/2 activation (22). NPY has also been shown to exhibit an inhibitory effect on isoprenaline-induced osteoclastogenesis by suppressing RANKL expression in mouse bone marrow cells (54).…”
Section: Npy and Bone Resorptionmentioning
confidence: 99%
“…Y1R has also been reported to be involved in many physiological activities, such as mitogenic activity, macrophage migration, and pulpal development ( 17 , 21 , 22 ). In bone tissue, Y1R is highly expressed in BMSCs, osteoblast, osteocyte, monocyte/macrophage, and osteoclast ( 2 ), prompting it to play a regulatory role in the local area.…”
Section: Neuropeptide Y and Its Receptorsmentioning
confidence: 99%
“…M2-type macrophages in VS are associated with angiogenesis and tumor growth [ 25 ]. Collagen cleavage leads to increased macrophage adhesion and promotes macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PD98059, an ERK1/2 inhibitor, reduced NPY-induced MMP-8 expression. Additionally, NPY promoted macrophage migration in vitro [ 43 ]. Park et al demonstrated that NPY induces macrophage PI3K/Akt/mTOR/eIL4E signalling pathway activation, which results in the production of transforming growth factor (TGF), leading to the upregulation of TGF-β expression and secretion by macrophages [ 44 ].…”
Section: Npy and The Inflammatory Microenvironmentmentioning
confidence: 99%